L’administration Eisenhower et la politique d’isolement contre Cuba - Salim Lamrani (Études Caribéennes)
In July 1960, the United States imposed the first economic sanctions against Cuba by removing the sugar quota, which was the main source of income for the island. Aware of the unpopularity of their foreign policy in Latin America, where most countries favored the free self-determination of peoples, Washington tried to persuade public opinion that Cuba had become an outpost of international communism on the continent and that a collective response to this threat was needed through the Organization of American States, an entity historically subordinate to the will of the White House.